Degradation of Methylene Blue Using Hydrothermally Synthesized α-Manganese Oxide Nanostructures as a Heterogeneous Fenton Catalyst. (22nd August 2022) - Dawadi, Sonika; Gyawali, Kabita; Katuwal, Saurav; Gupta, Aakash; Lamichhane, Ganesh; Khadka, Sujan; Koirala, Agni Raj; Parajuli, Niranjan
Abstract : Lately, the upsurge in the liberation of synthetic dyes into the environment, primarily by the textile industries, is a threat to the natural habitat and existing ecosystem. Various methods such as adsorption and degradation with nanoparticles are currently being used to degrade those hazardous materials, but still, the yearning for novel methods continues. In this study, hydrothermal reactions were performed at 160°C to synthesize manganese dioxide nanostructures (MnNSs) under different incubation periods that facilitated the comparison of the size, morphology, and crystallinity of MnNSs. The study revealed the change in crystallinity over the incubation period; MnNSs prepared at 24 hrs were highly crystalline among others. Additionally, the size and morphology of MnNSs changed from the sea-urchin or flower-like structure, predominantly sheet/layer form, to nanorods as the reaction proceeded for 24 hrs. Characterization of MnNSs was followed by heterogeneous Fenton's reaction, using α -manganese dioxide nanostructures, for the degradation of methylene blue (MB). To further understand the catalytic activity of MnNSs, the synthesized nanostructures were subjected to degrade MB at varied time intervals, both with and without hydrogen peroxide (H2 O2 ). Catalytically, MnNSs evinced good potential for degrading MB dye in the presence of H2 O2 ; MnNSs prepared at 24 hrs degraded MB up to 73% within 110 minutes.